PERAN KEPATUHAN KUNJUNGAN ANTENATAL CARE TERHADAP KOMPLIKASI KEHAMILAN DI KOTA BANDAR LAMPUNG - Jordan Tawarikh Hutabarat (Nusantara Hasana Journal, 2025)
This study aims to understand the relationship between antenatal care (ANC) visit adherence and the incidence of pregnancy complications among pregnant women in Bandar Lampung City. The background of this study is based on the importance of regular prenatal checkups as a preventive measure in maintaining maternal and fetal health. However, in many urban areas, maternal adherence to ANC visit schedules still varies due to different social, economic, and family support factors. This study used an observational analytical approach with a cross-sectional design. The population consisted of pregnant and postpartum women registered at health care facilities, with sampling using stratified multistage sampling. Analysis was conducted to assess the effect of ANC adherence on the potential for pregnancy complications by considering factors such as age, nutritional status, education, parity, and family support. The results are expected to provide a deeper understanding of the importance of ANC adherence as part of a maternal complication prevention strategy. The implications of this study emphasize the need for an integrative, family-based maternal health care approach oriented toward nutrition education and social support for pregnant women in urban areas.